Golgi-to-plastid trafficking of proteins through secretory pathway: Insights into vesicle-mediated import toward the plastids. (1st September 2016) - Baslam, Marouane; Oikawa, Kazusato; Kitajima-Koga, Aya; Kaneko, Kentaro; Mitsui, Toshiaki
ABSTRACT: The diversity of protein targeting pathways to plastids and their regulation in response to developmental and metabolic status is a key issue in the regulation of cellular function in plants. The general import pathways that target proteins into and across the plastid envelope with changes in gene expression are critical for plant development by regulating the response to physiological and metabolic changes within the cell. Glycoprotein targeting to complex plastids involves routing through the secretory pathway, among others. However, the mechanisms of trafficking via this system remain poorly understood. The present article discusses our results in site-specific N -glycosylation of nucleotide pyrophosphatase/phosphodiesterases (NPPs) glycoproteins and highlights protein delivery in Golgi/plastid pathway via the secretory pathway. Furthermore, we outline the hypotheses that explain the mechanism for importing vesicles trafficking with nucleus-encoded proteins into plastids.